The Writer's Presence : (Bedford/St. Martin’s, 2003)
The readings in The Writer’s Presence are selected exclusively for the quality of the writing. Editors Donald McQuade of the University of California, Berkeley, and Robert Atwan, Series Editor of The Best American Essays scoured hundreds of essays in search of teachable readings with strong voices and clear points of view. The result is a blend of classic pieces by favorites like James Baldwin, Annie Dillard, and Amy Tan; and fresh pieces by rising stars like Michael Pollan, Geeta Kothari, James McBride, and Daniel Harris. The voices in The Writer’s Presence represent different communities, time periods, levels of difficulty, and fields of study, and the topics intersect in intriguing and nuanced ways, giving students the opportunity to think critically and develop their own voices. Organized by type of writing and with minimal apparatus, The Writer’s Presence gives instructors unsurpassed teaching flexibility. With so many exceptional readings and so many ways to teach them, the possibilities are endless.